2016
DOI: 10.1590/1519-6984.13914
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and larval development of Brycon amazonicus (SPIX & AGASSIZ, 1829)

Abstract: The objective of this study was to describe the embryonic and larval development of Brycon amazonicus, featuring the main events up to 50 hours after fertilization (AF). The material was provided by the Aquaculture Training, Technology and Production Center, Presidente Figueiredo (AM). The characterization was based on stereomicroscopic examination of the morphology of eggs, embryos and larvae and comparison with the literature. Matrinxã eggs are free, transparent, and spherical, with a perivitelline space of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
8
0
4
Order By: Relevance
“…Nakauth et al . () observed that B. amazonicus larvae at 33 hph also have a partially pigmented retina and continuous movements of the jaw. These characteristics demonstrate that at this period B. amazonicus larvae are capable of active predation, which may initially result in high energy expenditure, which probably accelerates yolk‐sac consumption, already greatly reduced by then, leading to complete expenditure after a few hours.…”
Section: Discussionmentioning
confidence: 98%
“…Nakauth et al . () observed that B. amazonicus larvae at 33 hph also have a partially pigmented retina and continuous movements of the jaw. These characteristics demonstrate that at this period B. amazonicus larvae are capable of active predation, which may initially result in high energy expenditure, which probably accelerates yolk‐sac consumption, already greatly reduced by then, leading to complete expenditure after a few hours.…”
Section: Discussionmentioning
confidence: 98%
“…For example, skeletal ossification of pacu (Piaractus mesopotamicus) larvae is complete when larvae reach 40 post-hatching days (DPH) (Portella et al 2014), whereas in Brycon orbignyanus ossification is complete in larvae with 7 DPH (Maciel et al 2010). Thus, the fast larval development in B. amazonicus (e.g., Neumann 2008;Nakauth et al 2016) may modulate the display of aggressive behavior in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Matrinxã larvae hatch 10.5 hours after fertilization, exhibiting erratic vertical swimming characterized by upward movement, followed by constant sinking in the water column (Nakauth et al 2016). The oral cavity opens at 18 HAH, the mouth of larvae is completely opened, with sharp teeth and start of cannibalism at 30-34 HAH, 40 -70% of the yolk sac is apparently absorbed at 40 HAH, and more than 90% of the calf is absorbed at 60 HAH, with swim bladder inflation and horizontal swimming, suggesting greater control of swimming activity (Nakauth et al 2016). The early stages of development affected individual aggression in both our treatments, with highest rates of aggressive behavior observed at 12 HAH.…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest problems in the culture of this species is related to high mortality at the larval stage when cannibalistic behaviour has been indicated as the main cause of death (Leonardo et al, 2008). However, other reasons are also related to low survival in the larviculture, such as lack of knowledge about their ontogeny, inadequate nutrition composition of fish foods, bad environmental conditions and unknown digestive capacity (Cuenca-Soria et al, 2013;Nakauth et al, 2016;Alveal et al, 2019). Upon hatching, fish larvae nutrition occurs through absorption from the yolk sac and, generally, their organic systems are simple and incomplete.…”
Section: Introductionmentioning
confidence: 99%